Cultural Guidelines for Commercial Production of Interiorscape Calathea - Jianjun Chen; Dennis B. McConnell (EDIS)
ENH-1030, a 4-page fact sheet by Jianjun Chen and Dennis B. McConnell, provides producers with information about growing Calathea (Peacock Plant), including a table of cultivars, cultural guides for propagation and production, shipping and interior care, and a table of physiological problems. Published by the UF Department of Environmental Horticulture, November 2006.